Eponyms in anatomy of human urinary and genital systems - Svitlitsky , A.O.; Chernyavskiy , A.V.; Matvieishyna , T.M.; Shcherbakov , M.S.; Zinych , O.L.; Chugin , S.V. (Морфологія / Morphologia / Morfologìâ, 2025)
As experience showed, the exclusion of eponyms and eponymic terms from the international anatomical nomenclature in 1955 did not lead to their complete exclusion from both practical medicine, where they continue to be widely used and from anatomical science in particular. Moreover, the return of some eponymy terms in international anatomical terminology - Terminologia Anatomica, testifies to their great scientific, practical and historical significance, which confirms the relevance and expediency of the proposed research. The purpose of the study was to analyze the eponymic terms of anatomy of human urinary and reproductive systems in order to study, systematize and exclude errors. The search and selection of literature for systematic review is carried out by authors independently in the databases of PubMed, Scopus and Cochrane by the key words "Eponym", "Anatomical Terminology", "Urinary System", "Male Genitalia", "Female Genitalia" in full-text of articles in English and Ukrainian according to the results of research with the level of evidence I - III. The analysis found 21 eponymic terms, which is related to the genitourinary system, which was present in the first editions of the international anatomical nomenclature - Baseler Nomina Anatomica (BNA) - and is still found in ukrainian publications on human anatomy. A number of terms found in BNA were completely excluded from modern anatomical terminology, however, Latin equivalents are present in the international embryological - Terminologia Embryologica - and international histological - Terminologia Histologica - terminology. About 22 eponymic terms, which are reflected in Terminologia Anatomica and are used in clinical practice and literature, but are not available in modern Ukrainian anatomical nomenclature. All eponymous terms are ordered by sections and according to the alphabet, information about the researchers after which they were named and the corresponding Latin name with the designation of the nomenclature in which they occur. As a result of the analysis of more than 100 anatomical eponyms and eponymic terms of the structures of the urinary and genital systems, among them are about 20, which are presented in all major reviews of anatomical terminology and nomenclature including BNA. Official Latin synonyms were found for all eponym terms. Despite the complete exclusion of eponyms from the Paris anatomical terminology, they are actively used in medicine, namely in urology and gynecology, which makes them advisable to further study and systematize them.